2017
DOI: 10.2217/epi-2017-0078
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Of Methylation Levels Measured Using Illumina 450K And EPIC Beadchips In Blood Samples

Abstract: Aim:We examined concordance of methylation levels across the Illumina Infinium HumanMethylation450 BeadChip and the Infinium MethylationEPIC BeadChip.Methods:We computed the correlation for 145 whole blood DNA samples at each of the 422,524 CpG sites measured by both chips.Results:The correlation at some sites was high (up to r = 0.95), but many sites had low correlation (55% had r < 0.20). The low correspondence between 450K and EPIC measured methylation values at many loci was largely due to the low variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
127
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(150 citation statements)
references
References 26 publications
21
127
1
1
Order By: Relevance
“…Results for overall correlations in children corroborate studies in adult blood [4] and cancer tissue [1], which show overall correlation coefficients greater than 0.9. Also, similar to the study in adult blood, individual site correlations were much lower in the newborns and children in our study.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Results for overall correlations in children corroborate studies in adult blood [4] and cancer tissue [1], which show overall correlation coefficients greater than 0.9. Also, similar to the study in adult blood, individual site correlations were much lower in the newborns and children in our study.…”
Section: Discussionsupporting
confidence: 82%
“…Kling et al also reported high overall correlations between EPIC and 450K in both fresh-frozen and formalin-fixed paraffin embedded tumors [3]. Similar results were reported for overall correlation in adult whole blood (n = 145); however, low correlation was observed for many individual sites (55% with r <0.2) and were found to correspond with the variance or range of methylation at a site [4]. Studies comparing the two platforms in samples collected from children have not yet been reported.…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations